2021
DOI: 10.5194/acp-21-13031-2021
|View full text |Cite
|
Sign up to set email alerts
|

A global study of hygroscopicity-driven light-scattering enhancement in the context of other in situ aerosol optical properties

Abstract: Abstract. The scattering and backscattering enhancement factors (f(RH) and fb(RH)) describe how aerosol particle light scattering and backscattering, respectively, change with relative humidity (RH). They are important parameters in estimating direct aerosol radiative forcing (DARF). In this study we use the dataset presented in Burgos et al. (2019) that compiles f(RH) and fb(RH) measurements at three wavelengths (i.e., 450, 550 and 700 nm) performed with tandem nephelometer systems at multiple sites around th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…It is interesting to find that the dust ARFETOA over East Asia is apparently higher than that over South Asia, which could be indicative of the different compositions of dust that lead to different absorbing capabilities. Comparatively, the U/I aerosols could be more influenced by the moisture conditions which are related to the hygroscopicity of U/I aerosols [67]. We could find noticeable differences in the ARFETOA of U/I aerosol between continental sites and coastal or marine sites.…”
Section: Aerosol Radiative Forcing and Radiative Forcing Efficiencies...mentioning
confidence: 86%
“…It is interesting to find that the dust ARFETOA over East Asia is apparently higher than that over South Asia, which could be indicative of the different compositions of dust that lead to different absorbing capabilities. Comparatively, the U/I aerosols could be more influenced by the moisture conditions which are related to the hygroscopicity of U/I aerosols [67]. We could find noticeable differences in the ARFETOA of U/I aerosol between continental sites and coastal or marine sites.…”
Section: Aerosol Radiative Forcing and Radiative Forcing Efficiencies...mentioning
confidence: 86%
“…Previous studies found that the magnitude of the RFE increases with increasing b (Shen et al, 2018). Typical values of b for the atmospheric aerosol at 550 nm were from approximately 0.05 to 0.20 (Titos et al, 2021).…”
Section: Introductionmentioning
confidence: 92%
“…As a result, nighttime AOD (0.45 ± 0.47) displayed larger mean values than during the day (0.40 ± 0.29). The large mean and standard deviation of nighttime AOD can be attributed to the nighttime formation of nitrate from the nocturnal processing of nitrogen oxides (H. Kim et al., 2018), a build‐up of pollutants due to stagnant atmospheric conditions within the nocturnal BL (Ma et al., 2017), and enhancement of aerosol extinction due to hygroscopic growth of aerosols (Eck et al., 2014; Titos et al., 2021; Ziemba et al., 2013).…”
Section: Temporal Variation Of Boundary Layer (Bl) and Free‐troposphe...mentioning
confidence: 99%
“…Uncertainties in aerosol optical property simulations of the model will affect the validation results of CTMs. Due to the large diversity in aerosol optical properties as a function of aerosol species (Kinne et al., 2006; Nemuc et al., 2013) and ambient relative humidity (RH; Pérez‐Ramírez et al., 2021; Titos et al., 2021), measurement‐based validation of the aerosol modules of CTMs is necessary (Hand & Malm, 2007; Saide et al., 2020).…”
Section: Introductionmentioning
confidence: 99%